1984
DOI: 10.1068/p130505
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Feature Displacement on Face Recognition

Abstract: Human beings possess a remarkable ability to recognise familiar faces quickly and without apparent effort. In spite of this facility, the mechanisms of visual recognition remain tantalizingly obscure. An experiment is reported in which image processing equipment was used to displace slightly the features of a set of original facial images to form groups of modified images. Observers were then required to indicate whether they were being shown the "original" or a "modified" face, when shown one face at a time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0
3

Year Published

1990
1990
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(74 citation statements)
references
References 12 publications
2
69
0
3
Order By: Relevance
“…Other studies suggest that brain regions thought to be mainly engaged in face recognition can be activated by non-facial stimuli in experts (Tarr and Gauthier 2000). In human faces, changes in the second-order relationship between features is known to be easily detected (Haig 1984;see Maurer et al 2002 for a review). Interestingly, recent work has shown that learning to recognise non-facial stimuli at the individual level leads to a higher sensitivity to second-order relationships between features of the stimuli in experts (Nishimura and Maurer 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Other studies suggest that brain regions thought to be mainly engaged in face recognition can be activated by non-facial stimuli in experts (Tarr and Gauthier 2000). In human faces, changes in the second-order relationship between features is known to be easily detected (Haig 1984;see Maurer et al 2002 for a review). Interestingly, recent work has shown that learning to recognise non-facial stimuli at the individual level leads to a higher sensitivity to second-order relationships between features of the stimuli in experts (Nishimura and Maurer 2008).…”
Section: Introductionmentioning
confidence: 98%
“…First, conWgural information may refer to metric distances between facial features such as the interocular or eye-mouth distance. These distances between facial features can be measured and manipulated on the stimulus, and the sensitivity of the face processing system to perceive and encode this information can be tested in discrimination or recognition tasks (e.g., Barton, Keenan, & Bass, 2001;Freire, Lee, & Symons, 2000;Haig, 1984;Leder, Candrian, Huber, & Bruce, 2001). The second type of conWguration is referred to as holistic processing.…”
Section: Introductionmentioning
confidence: 99%
“…While this is efficient, it has consequences for how facial information is perceived: for example, individual features are recognised better within the context of the whole face image (Tanaka & Farah, 1993), but alterations to a facial configuration will impair recognition of the individual features (Tanaka & Sengco, 1997). Sensitivity to familiar faces (Haig, 1984;Hosie, Ellis, & Haig, 1988) means that any changes to the configuration will alter holistic perception of the whole image and the face will appear different (Tanaka & Sengco, 1997). Wilford and Wells (2010) showed that holistic face perception enhances detection of any face alteration but makes it difficult to identify what feature has changed.…”
Section: Holistic Processing Can Impair Identification Of Forensic Famentioning
confidence: 99%